Real-time Evaluation System of Monitoring Equipment State Based on the Integration of Subjective and Objective. (September 2020) - Qi, Jingxian; Cao, Yuefeng; Sha, Shuming
Abstract: Equipment operation monitoring is an important means to ensure the safe operation of power grid, and the operation status of power equipment will directly affect the operation security of power grid, so it is necessary to evaluate the equipment status in real time. In this paper, a subjective and objective evaluation system based on AHP and entropy weight method is proposed, which integrates the operation information and model information of power grid equipment and defines the indicator system of multi-dimensional analysis. The results show that this method has a very good guiding role in ensuring the real-time evaluation of equipment and the auxiliary decision-making of regulation and control